Cellulose acetate membranes for osmosedimentation: Performance and morphological dependence on preparation conditions - Nunes, Suzana Pereira; Galembeck, Fernando; Barelli, Nilso [UNESP] (Elsevier B.V., 1986)
Osmosedimentation is a new membrane-assisted separation technique, based on the rapid approach to sedimentation equilibrium when macromolecular solutions are contained within dialysis cells, in contact with solvent via a permselective membrane. Cellulose acetate membranes, cast from ternary solvent (acetone, acetic acid, water) solutions are suitable for osmosedimentation of proteins at low (2000 rpm) centrifugation speeds. Solute retention is improved when acetone-rich casting solutions are used. These membranes were examined by electron and optical microscopy, showing considerable morphological changes in the membrane support layer as the casting solution composition is changed. © 1986.
Keywords: Membrane morphology; Osmosedimentation; Cellulose derivatives - Applications; Diaphragms - Morphology; Microscopic Examination; Proteins - Separation; Casting solvent; Cellulose acetate membranes; Membrane morphology; Osmosedimentation; Membranes